2015
DOI: 10.3758/s13420-015-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the discriminative properties of the reinforcer in resurgence

Abstract: Three experiments with rat subjects examined the effects of the discriminative effects of reinforcers that were presented during or after operant extinction. Experiments 1 and 2 examined resurgence, in which an extinguished operant response (R1) recovers when a second behavior (R2) that has been reinforced to replace it is also placed on extinction. The results of Experiment 1 suggest that the amount of R1’s resurgence is a decreasing linear function of the interreinforcement interval used during the reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
75
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 39 publications
(96 reference statements)
16
75
3
1
Order By: Relevance
“…In a complementary way, rats first tested with O1 presentations showed a significant renewal effect, whereas rats first tested with O2 presentations did not. This pattern, coupled with previous findings suggesting that reinforcers delivered independently of responding during or after extinction do not usually suppress responding (e.g., Baker, 1990; Bouton & Trask, 2015; Rescorla & Skucy, 1969; Winterbauer & Bouton, 2011), suggests that in order for a reinforcer to attenuate ABA renewal, it needs to be a feature of extinction learning. The results are not consistent with the idea that the results of Experiment 1 were due to O2 unconditionally eliciting competing behaviors, or otherwise disrupting operant responding (e.g., Shahan & Sweeney, 2011); in that case, O1 should have been equally effective here.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In a complementary way, rats first tested with O1 presentations showed a significant renewal effect, whereas rats first tested with O2 presentations did not. This pattern, coupled with previous findings suggesting that reinforcers delivered independently of responding during or after extinction do not usually suppress responding (e.g., Baker, 1990; Bouton & Trask, 2015; Rescorla & Skucy, 1969; Winterbauer & Bouton, 2011), suggests that in order for a reinforcer to attenuate ABA renewal, it needs to be a feature of extinction learning. The results are not consistent with the idea that the results of Experiment 1 were due to O2 unconditionally eliciting competing behaviors, or otherwise disrupting operant responding (e.g., Shahan & Sweeney, 2011); in that case, O1 should have been equally effective here.…”
Section: Discussionsupporting
confidence: 70%
“…It is worth noting that the earlier studies did not use different reinforcers in conditioning and extinction as we did here. However, in a related design, Bouton and Trask (2015; Experiment 3) found that animals that received free presentations of an O2 reinforcer during extinction after initial acquisition with O1 likewise showed no augmenting effect of O1 presentations during a final test. Given these results, it seems that free reinforcer presentations in extinction may have an effect on the ability of similar reinforcers to augment or reinstate extinguished responding.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, Sweeney and Shahan (2013a) also found no evidence of resurgence following a VI 100-s reinforcement schedule. A recent study in our laboratory (Bouton & Trask, 2015) found significant resurgence following VI 30-s and VI 60-s schedules of reinforcement for R2 during Phase 2, but no resurgence in groups that received relatively lean VI 90-s and VI 120-s rates over the phase. Moreover, the strength of resurgence was shown statistically to be a decreasing linear function of the VI parameter.…”
Section: Evaluating the Theoriesmentioning
confidence: 81%